Event Study Of The New Economy Board On Abnormal Return And Trading Volume Activity Of Company Shares In The Indonesia Stock Exchange - Agung Setiawan; Yoyo Sudaryo; Dayan Hakim Natigor Sipahutar; Nunung Ayu Sofiati (Green Publisher Indonesia, 2024)
The research window for this study is 11 days, which includes 5 days prior to the event, 5 days after the incident, and an estimated 14 days after the event. The type of research in this study is an event study. In this case, the independent variable (variable X) is the event of launching the New Board Economic whereas the dependent variables (variable Y) are abnormal return and trading volume activity. The research sample consists of companies listed on the new economic listing board. The companies included in the sample are GOTO, BUKA, and BELI. Hypothesis testing is done using One Sample T-Test and Paired Sample T-Test. The research results show that the significance value of abnormal return on T-5 is <0.05, whereas for other periods it is >0.05. Similarly, all periods of trading volume activity show values >0.05. This indicates that there is a significant abnormal return on T-5, or 5 days before the event of the launch of the New Economic Board. Meanwhile, in other periods, there is no significant abnormal return, and none of the periods show significant trading volume activity. In the difference test, the Sig. (2-tailed) values for both abnormal return and trading volume activity are >0.05, indicating no difference in abnormal return before and after the launch of the new economic board, as well as no difference in trading volume activity.